Dynamic Production of Soluble Extracellular Polysaccharides by Streptococcus mutans - Eva-Maria Decker; Ilka Dietrich; Christian Klein; Christiane von Ohle (Hindawi Limited, 2011)
Caries development in the presence of Streptococcus mutans is associated not only with the production of extracellular water-insoluble polymers but also is based on water-soluble polysaccharides. The aim of this study was the evaluation of a novel glucan-specific Lectin assay for monitoring water-soluble EPS produced by S. mutans during several growth periods in different media. S. mutans cultures were grown for 24 h, 48 h, and 144 h in medium deficient of sucrose (A) and medium supplemented with 5% sucrose (B). Microtiter well plates were coated with cell-free supernatants followed by the addition of labeled Concanavalin-A and enzyme substrate. The substrate reactions were kinetically detected at 405 nm. The validation of the assay was performed using carbohydrates dextran, xanthan, and sucrose as reference. This new Concanavalin-A-based assay showed the highest sensitivity for dextran and revealed that the glucan production of S. mutans reached its maximum at 144 h in medium B according to bacterial maturation.